Design of Small Business Licensing Information System PTSP Kelurahan Pulogadung Jakarta: Design of Small Business Licensing Information System PTSP Kelurahan Pulogadung Jakarta - Dina Ayu Ariyani; Eva Zuraidah (Jurnal Mantik, 2020)
The demand for better and more satisfying public services for the people is a need that must be met by the government. The One-Stop Integrated Service Office is a Pulogadung village government agency tasked with providing licensing services, one of which is the making of micro-small business licensing which is considered less effective and efficient because the process is still done manually. The purpose of this research is to create an information system for licensing and request for licensing recommendations at the Pulogadung Village PTSP Office on a web-based basis to provide better services. The system development model used is the waterfall method and structured analysis modeling. In making this information system there are two requirements analysis needed, namely, software analysis and system design analysis. This system is made with PHP, SQL, Javascript and to arrange website structure using HTML and CSS programming languages. With the web-based information system design in the Pulogadung Village PTSP Office, it is expected to provide convenience to the public who want to open a business in managing micro-small business permits. Besides that, employees can manage the application data submitted by the applicant quickly and accurately and transparently, this study using the waterfall methodology